Global meta-data comparing the abundance and species richness of non-domesticated biodiversity in diversified and simplified farming systems - Sanchex Bogado, Andrea Cecilia (2021)
Global meta-data including 2258 comparisons (from 161 articles), of which 1886 (129 articles) measured abundance, and 372 (65 articles) measured richness in diversified and simplified farming systems. (2021-09-21)